House and garden : fifties house - Gray, Catriona; Conran, Terence (London, United Kingdom : Conran Octopus, 2014)
The first title in a series covering twentieth-century interiors by decade using original material from the British House & Garden's peerless archive. The post-war consumer boom of the 1950s, coupled with a desire for new, innovative design resulted in one of the most exciting decades in the history of interiors - a visual revolution that was captured on the pages of British House & Garden. In Fifties House, mid-century modern enthusiast Catriona Gray has drawn on the magazine's peerless archive, curating the best illustrations and photographs to show how the use of color, pattern, home-wares and furniture evolved through the decade. The homes of key taste-makers are featured including Le Corbusier, Giò Ponti, Terence Conran and Hans and Florence Knoll. The first title in the new Decades of Design series, House & Garden Fifties House is required reading for mid-century modern enthusiasts, collectors and decorators in search of inspiration from the most influential homes of the past.
Foreword by Terence Conran -- Introduction -- 1. Rooms -- 2. Houses -- 3. Decoration -- Bibliography and Stockists -- Picture credits -- Index.
Includes bibliographical references and index.
Keywords: INTERIOR DESIGN